MAKNA FRASA "TAKUT AKAN TUHAN" DALAM KEKRISTENAN MODERN:: PERSPEKTIF DAN IMPLEMENTASI BERDASARKAN AMSAL 1:7 - Simatupang, Rut Desinta; Gulo, Refamati (Jurnal Teologi RAI, 2024)
The phrase “Fear of the Lord” that repeatedly appears in the Book of Proverbs, particularly in Proverbs 1:7 which reads, “The fear of the Lord is the beginning of knowledge,” carries deep theological significance in the Christian tradition. This phrase not only affirms the beginning of divine wisdom, but also describes the heart attitude that believers should have in knowing and worshipping God. However, in the context of modern Christianity, the relevance and application of this concept is often a matter of discussion, given the cultural shifts and spiritual challenges faced by Christians today. This study aims to analyze the meaning of the phrase “fear of the Lord” in the context of modern Christianity, as well as explore how views and practices related to this phrase are applied in contemporary Christian life. In addition, this study also highlights how the concept of “fear of the Lord” undergoes changes or adjustments in line with the dynamics and challenges of the evolving times. This study uses a method with a theological and hermeneutic analysis approach to the biblical text, particularly Proverbs 1:7, to explore the meaning of the phrase “fear of the Lord” in the context of modern Christianity. Through textual analysis, the study examined classical and modern interpretations of relevant biblical passages, in order to understand how the phrase is translated and applied in contemporary Christian life. Thus, the results of this study show that the “fear of the Lord” is defined as reverence, awe, and obedience to God, not just literal fear. This understanding is manifested in life attitudes that reflect integrity, ethics, and morality according to the teachings of Christ. Thus, it can be implemented in various forms of spiritual and social activities, including religious education, worship, and daily spiritual practices such as prayer and meditation. This research also shows that the concept of the “fear of the Lord”, when properly understood and consistently applied, has the potential to deepen the spiritual life of Christians. Moreover, a proper understanding of this concept can be a source of strength and guidance for Christians in facing the challenges of daily life.